Morality of atheism and immorality of theism in the light of Paul-Henri Holbach’s philosophy - Szocik, Konrad (Hybris, 2016)
This paper presents some reflections referred to the alleged advantage of the atheistic morality over the theistic morality. It refers especially to the philosophy of religion and morality developed by Paul Henri-Holbach. His main idea states that religion has negative impact on the human natural morality.